2006
DOI: 10.1186/1477-7827-4-59
|View full text |Cite
|
Sign up to set email alerts
|

Molecular patterns of sex determination in the animal kingdom: a comparative study of the biology of reproduction

Abstract: Determining sexual fate is an integral part of reproduction, used as a means to enrich the genome. A variety of such regulatory mechanisms have been described so far and some of the more extensively studied ones are being discussed.For the insect order of Hymenoptera, the choice lies between uniparental haploid males and biparental diploid females, originating from unfertilized and fertilized eggs accordingly. This mechanism is also known as single-locus complementary sex determination (slCSD). On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…26 This temperature effect on the fruit fly gender falls under the domain of thermosensitive sex selection, which is frequently used in zoology of fish and reptiles. 27 Chronic cold exposure can shift the sex ratio toward a male-biased extreme, 28 whereas spiroplasma endosymbionts, the maternally inherited micro-organisms that infect arthropod species including Drosophila and act as reproductive manipulators by killing exclusively sons of infected mothers may be a factor involved in this variation. 29 Genotoxic effects have been observed in Drosophila dosed with inorganic nanoparticles, 3032 but they are improbable to occur with CPs, especially at the low concentration in media of 0.3 wt % used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…26 This temperature effect on the fruit fly gender falls under the domain of thermosensitive sex selection, which is frequently used in zoology of fish and reptiles. 27 Chronic cold exposure can shift the sex ratio toward a male-biased extreme, 28 whereas spiroplasma endosymbionts, the maternally inherited micro-organisms that infect arthropod species including Drosophila and act as reproductive manipulators by killing exclusively sons of infected mothers may be a factor involved in this variation. 29 Genotoxic effects have been observed in Drosophila dosed with inorganic nanoparticles, 3032 but they are improbable to occur with CPs, especially at the low concentration in media of 0.3 wt % used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…It has long been proposed that epigenetic regulation may play an important role in ESD species in response to environmental influences, leading to the gonad developmental change (Manolakou et al 2006). Plenty of experiment results suggested that epigenetic regulation plays multiple crucial roles in the gonadal differentiation of teleosts and other vertebrates (Navarro-Martin et al 2011, Zhang et al 2013, Parrott et al 2014, Shao et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of environmental and genetic factors in sex regulation, a mechanism more common to fish than previously recognized [44], seems the most plausible explanation for our results. Epigenetic regulation of gene expression during gonad differentiation is involved in the adaptive sex reversal observed in some fish and other organisms with genetic sex determination [45]. For example, methylation has been related to sexual reversal in relation to incubation temperature in the half-smooth tongue sole [36].…”
Section: Discussionmentioning
confidence: 99%